Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai PT BPR Kartasura Saribumi Cabang Masaran - Trisnowati, Juni (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
This study analyzes the influence of motivation and discipline to the performance of employees of PT BPR Kartasura Saribumi Cabang Masaran. The problems are formulated is: is there asignificant relationship between motivation and discipline to employee performance either partially or simultaneously. The hypothesis is